2009
DOI: 10.1002/app.30875
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the spinning conditions on the structure and properties of polyamide 12/carbon nanotube composite fibers

Abstract: The inclusion of nanoparticles in polymer fibers is potentially useful for improving or bringing new properties such as mechanical strength, electrical conductivity, piezoresistivity, and flame retardancy. In this study, composite fibers made of polyamide 12 and multiwall carbon nanotubes were investigated. The fibers were spun via a melt-spinning process and stretched at different draw ratios. The influence of several spinning factors, including spinning speed, extrusion rate, and draw ratio were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 59 publications
4
19
0
Order By: Relevance
“…In contrast, p‐MWNT based composite fiber could not be drawn beyond a critical value of DR largely due to the less interfacial interaction between p‐MWNT and PP. In contrast, PA12/MWNT composites exhibited higher tensile modulus at 5 and 7 wt% MWNT with increase in orientation factor, which was achieved through the use of hot drawing using tensile tester device [30]. Moreover, it is also expected that the state of dispersion of a‐MWNT would be better as compared to p‐MWNT in the corresponding composites in the current context.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, p‐MWNT based composite fiber could not be drawn beyond a critical value of DR largely due to the less interfacial interaction between p‐MWNT and PP. In contrast, PA12/MWNT composites exhibited higher tensile modulus at 5 and 7 wt% MWNT with increase in orientation factor, which was achieved through the use of hot drawing using tensile tester device [30]. Moreover, it is also expected that the state of dispersion of a‐MWNT would be better as compared to p‐MWNT in the corresponding composites in the current context.…”
Section: Resultsmentioning
confidence: 99%
“…They also show a uniquely high thermal conductivity of 2800-6000 W/ mK at room temperature [1,2] , which is greater than those of graphite and carbon fibers. It has been reported that CNT acts as an efficient nucleating agent on polymers, including polypropylene (PP) [3,4] , nylon [5,6] , poly(phenylene sulfide) (PPS) [7][8][9] , and polyolefins [10] , and accelerates the crystallization process. It has been observed that the crystallinity of polymer has a very important influence on the thermal performance.…”
Section: Introductionmentioning
confidence: 99%
“…A significant improvement of the storage modulus (+40%) was achieved by the dispersion of MWCNT‐OH in the PBT‐PTMO matrix. To our knowledge there are few examples of polymer nanocomposites based on commercially available polymeric matrices [namely poly(vinyl alcohol), poly(methyl methacrylate) or polycarbonate], which exhibit such an improvement in mechanical properties 67–71…”
Section: Resultsmentioning
confidence: 99%